Research on Intelligent Construction Technology Based on Green Concepts - Wang Kai (E3S Web of Conferences)
Compared with other industries, the construction industry has significant energy consumption characteristics. Therefore, actively promoting the green ecological construction in the construction industry is a crucial aspect to follow the current global low-carbon transformation call. This paper introduces intelligent building technology and its embodiment of green building concept. From the analysis of Building Information Modelling (BIM), intelligent building robot, Internet of Things (IoT) and other key technology fields, the significance of the combining of green and intelligent building is summarized. By conserving energy and reducing emissions, efficient use of resources, pollution reduction and other means. The construction industry is enriched by the birth of the construction industry Internet, construction robots, and other new industrial forms, which not only promotes resource conservation and environmental protection, but also promotes technological innovation and industrial upgrading. Meanwhile, these technologies improve building quality and user experience, create a safe, comfortable and convenient living and working environment, and extend the service life of buildings. Therefore, the active promotion and application of smart building technologies based on green concepts is of great significance for building a better and more sustainable future.